Early-stage endometrial carcinoma; risk factors for recurrence - Andleeb, Asifa; Fatima, Kaneez; Nasreen, Shahida; Sofi, Mushtaq Ahmad; Malik Tariq Rasool; Arshad Manzoor Najmi; Wani, Shaqul Qamar (Asian Journal of Medical Sciences, 2024)
Background: Endometrial carcinoma (EC) is the most common gynecological malignancy in developed countries. The overall prognosis is excellent, as most cases are diagnosed at an early stage with low-grade histology, but once the recurrence occurs, the median survival decreases severely. Aims and Objectives: The aim of this study was to identify the risk factors associated with recurrence in early-stage EC and explore their impact on overall survival (OS) after recurrence. Materials and Methods: Records from patients diagnosed with EC were retrospectively reviewed. 220 patients were identified as early-stage, low-risk EC who underwent primary surgical treatment between January 2010 and December 2022, and their baseline characteristics were analyzed. Cox regression analysis was used to identify various factors for tumor recurrence. Survival analysis was done using the Kaplan-Meier method. Results: In a cohort of 220 patients, we observed tumor recurrence in 44 (20%) patients and 34 (15.45%) deaths over a median follow-up of 72 months (range, 12–144 months). Multivariate analysis confirmed two risk factors: myometrial invasion (MMI) of any depth and lymphovascular invasion (LVI) as independent predictors of recurrence. The prognosis was worse for patients with recurrence than for those without. The OS for the recurrent group was 38.6%, compared to 96.0% in the non-recurrent group. In our study, the median time to recurrence was 19 months (confidence interval 18–30) months. Conclusion: The presence of MMI and LVI are important predictors for recurrence in early-stage low-risk EC.